Digital transformation in higher education - Zimonjić Marijana; Baltezarević Borivoje (Megatrend Revija, 2024)
The world faced a crisis in 2020 for which no one could have been prepared. The infectious disease COVID-19 affected the way we live and work. Countries had to shut down and impose social distancing measures to minimize infection rates and resulting deaths. Additionally, many public and private institutions, such as universities and schools, had to close their doors.[1] Rapid digitalization emerged as a result of social distancing.[2] Since digital technologies and organizational capabilities are the foundation of every digital transformation journey, it is easy to understand that IT inefficiency in responding to changes and supporting overall business transformation is a significant challenge. During the COVID-19 pandemic, universities faced a sudden need for digital transformation. Many transitioned to online teaching to continue the educational process, which posed a significant challenge for institutions unprepared for such changes. This transformation has altered the way universities operate and could pave the way for major changes in higher education.